Doctor Illuminatus - Booth, Martin (New York : Little, Brown, 2006)
Pip and her twin brother, Tim, awaken an alchemist's son from a centuries-long slumber when their family moves to an old English country estate, and he enlists them in the fight against an evil alchemist who seeks to create a homunculus.
7.2
5-8
5-8
School Library Journal
Booklist
Bulletin (Center for Children's books)
Keywords: Alchemy -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Twins -- Fiction; Adventure and adventurers -- Fiction; England -- Fiction; Alchemy -- Fiction; Magic -- Fiction; Siblings -- Fiction; Twins -- Fiction; Adventure fiction; England -- Fiction